THE ROLE OF ORGANIZATIONAL COMMITMENT IN MEDIATING THE RELATIONSHIP BETWEEN WORK CULTURE, HUMAN RESOURCE QUALITY, AND EMPLOYEE PRODUCTIVITY - M, Riahi; O, Azizan; M, Rasti-Barzoki (Economics and Statistics Research Journal (ESRJ), 2023)
This study explores the impact of work culture and human resource quality on employee productivity through the mediating role of organizational commitment. Using a sample of 55 employees from the agency for rural community empowerment, population arrangement, and women empowerment of Nagan Raya District in Indonesia, data was collected through a questionnaire and analyzed using structural equation modeling (SEM) through Smart-PLS software. Results indicate that work culture and human resource quality had a significant and positive effect on both organizational commitment and employee productivity. Additionally, organizational commitment was found to mediate the impact of work culture and human resource quality on employee productivity. These findings provide valuable insights for human resource practitioners in government agencies and add to the existing literature on the role of organizational commitment in mediating relationships between variables